CD-based childcare system (CDCS) - Tio, Siow Teng (University Malaysia Sarawak, UNIMAS., 2006)
This thesis details the development of CD-Based Children System (CDCS) for parents to take care of their child's health from Day. The CDCS provides parenting information in an interactive way using multimedia. Research has been undertaken on various CD-Based courseware and websites available in the market. CDCS consists of six general modules which are Contents module, Baby Record module, Quick Finder module, Games module, Setting module and Help module. The purpose of including Baby Record System is to help parents keep tracks their baby's development in a proper way. The development of this project uses the Multimedia Development Life Cycle (MDLC) and Macromedia Flash Professional 8.0 for its implementation.